Pengaruh Sistem Pengendalian Internal dan Pelaksanaan Audit Internal Terhadap Good Corporate Governance - Angelica Ade Virginia Irene Ginting; Wati Rosmawati; Shofia Asry (Jurnal Akuntan Publik, 2024)
The purpose of this research is to examine the influence of internal control systems and internal audit implementation on Good Corporate Governance (GCG). This study was conducted at PT. Pertamina Persero, using primary data obtained by distributing questionnaires to 30 personnel in the audit and financial management divisions. The analysis method used in this research is multiple linear regression analysis. The results from the t- test (hypothesis test) show that (1) the internal control system variable has a positive effect on good corporate governance, with a calculated t-value of 3.921, which is greater than the t-table value of 1.701, and a significance value of 0.001, which is less than 0.05. (2) The internal audit implementation variable does not significantly affect good corporate governance, with a calculated t-value of -0.829, which is less than the t-table value of 1.701, and a significance value of 0.414, which is greater than 0.05. (3) There is a positive and significant influence of the internal control system on good corporate governance, while the internal audit implementation does not significantly impact good corporate governance. This is evidenced by an R Square value of 0.649, indicating that 64.9% shows a significant influence, and the remaining 35.1% is influenced by other variables outside of this study.